An analytical study of the relationship between training variables and sports injuries and their causes in handball players - Youssef Mohamed, Mahmoud; Saleh Al-Jassas, Mazen (sports creativity, 2025)
This study aims to identify the relationship of some training variables to common sports injuries and their causes for handball players. The researchers used the descriptive method to suit the nature of the study on a sample of 138 players from the first division of the Premier League.